Effectiveness of instructional intervention upon multipara women’s practices to control stress incontinence - hussein, Wafaa; ali, Rabea (Iraqi National Journal of Nursing Specialties, 2012)
Objective(s): to determine the effectiveness of instruction intervention upon multipara women's practices tocontrol stress incontinence.Methodology: A quasi-experimental study was carried out from (2nd) April, 2010 to 15th June, 2010. Nonprobability(purposive sample) of (60) multiparous women was selected from Baghdad Teaching Hospital and AlElwiaMaternity Teaching Hospital in Baghdad city, the sample was divided into two groups (30) women wereconsidered as a study group, and another (30) were considered as the control group. An instructional interventionwas applied on the study group, while the intervention was not applied on control group. A questionnaire wasresolve as a tool of data collection to suit the purpose of the study. A pilot study was carried out to test thereliability and validity of the questionnaire for the period from 10th of March. - 30 March. 2010. Data wereanalyzed through the application of descriptive statistical data analysis approach (frequency, percentage, mean ofscores) and inferential statistical data analysis approach (correlation coefficient, and chi- square).Result: The results of the study revealed that the study group participants had benefited from the implementationof instructional intervention and dramatic change had occurred in their practices to control stress urinaryincontinence. The study concluded that the majority of mothers had adequately met their needs control stressurinary incontinence-pelvic floor and perineum muscles exercise, and lifestyle change.Recommendation: The study recommended that the instructional intervention can be presented to all multiparapregnant mothers who are attending to the primary health care centers; moreover, an instructional interventionmight be implemented in the hospital for multipara women to increase their knowledge about stress urinaryincontinence. The study also recommended that the nurse must take the role for teaching multiparous women theprinciples of control SUI while they perform such procedure for them during postpartum period.